Vicissitudes of the restoration company of the steel manufactory, named El Socorro, in Coalcoman, 1863-1875 (Tzintzun, Revista de Estudios Históricos, 2021)
This paper addresses the vicissitudes of the restoration process of the steel manufactory in Coalcomán. Established in 1806 by the mineralogist AndrésManuel del Río, it was destroyed during the independence war. A first attempt to restore it occurred a few years after Independence was consummated, however this did not succeed due to political unrest and to the continuous confrontations between federalists and centralists. In 1863, in the state of Colima, a company was established by a group of shareholders intending to restore CoalcomanÂ´s steel manufactory with the aim of producing iron to boost the countryâ€™s industrial development. The works were assigned to Francisco Nigoul, a welding technician of French descendant who was in charge of this project between 1869 and 1875. In this article we consider as well diverse studies that were carried out to measure the potential of the iron deposits located in the municipality of Coalcomán.
Keywords: steel manufactory; iron production; XIX century; Coalcomán